A UTHM Online Activity Management System - Zainal, Nurezayana; Choon, Chin Kar (Applied Information Technology And Computer Science, 2020)
At present, activity and venue application at Universiti Tun Hussein Onn Malaysia (UTHM) is managed by Hal Ehwal Pelajar dan Alumni (HEPA) and Pejabat PEngurusan Akademik (PPA). Application forms and related documents are in a paper-based file and handled manually by a staff of these two departments. However, this type of method is less effective especially when handling a huge number of applications because it takes a too long time to revise. Therefore, this study developed an online activity management system to help manage these kinds of jobs. This project will be developed by using the agile method and using web-based languages. By using this system, a club representative can upload their activity proposal and supporting documents. They can easily check the status of their presentation in this system. Besides, the administrator of HEPA can search and review the summary of each club. This project involved three users which are club representative, administrator of HEPA, and administrator of PPA. This developed system will improve the efficiency of activity management and summary retrieval. Therefore, the system is expected to improve the efficiency of activity management and reduce the usage of paper in applications.